ChemInform Abstract: PhI(OCOCF3)2‐Mediated Intramolecular Oxidative N—N Bond Formation: Metal‐Free Synthesis of 1, 2, 4‐Triazolo[1, 5‐a]pyridines. Issue 44 (4th November 2014) - Zheng, Zisheng; Ma, Shuangyu; Tang, Linlin; Zhang‐Negrerie, Daisy; Du, Yunfei; Zhao, Kang
Abstract The features of the title synthesis are the broad substrate scope, mild reaction conditions, high yields, and short reaction time.